ANALISIS TAX PLANNING UNTUK EFISIENSI PAJAK PENGHASILAN BADAN (STUDI PADA PT ABDYA GASINDO) - sumardi usman; Miftha Rizkina (Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this paper is to find out whether the application of tax planning carried out by PT. Abdya Gasindo can streamline corporate income tax. The writing method used is descriptive method that is the method that collects, collects the data obtained then is interpreted and analyzed so that it is able to provide complete information for problem solvers encountered. The results of this study are expected to provide information and input on Abdya Gasindo so that the company can carry out tax planning as an effort to efficiently pay taxes to achieve maximum profits, but still within the framework of tax regulations. The conclusion of this study is the application of tax planning conducted by PT. Abdya Gasindo can make efficient the tax burden owed.